ANALISIS BRAND EQUITY, BRAND AWARENESS, DAN ATTITUDE TERHADAP PURCHASE INTENTION AIR MINUM DALAM KEMASAN MEREK LE MINERALE (STUDI KASUS MAHASISWA DI UNIVERSITAS KRISTEN INDONESIA) - ., Meysyahdamay; Tobing, Fenny BNL. Tobing (Fundamental Management Journal, 2019)
Le Minerale is a brand of bottled mineral in Indonesia, purchased by PT. Tirta Fresindo Jaya which isa subsidiary of Mayora Indah, Engaged in the beverages sector. Brand equity, brand awareness, andattitudestowards consumers’ purchase intentionof the Le Minerale brand, to students atChristian University of Indonesia, Jakarta.The research method used by author is qualitative descriptive. For data analysis techniques carried out by author is usingquality test data (validity and reliability test) Spearman Rank test, and Likert Score to prove or know the statistical test. Keywords : brand equity, brand awareness, attitude, purchase intention, atittudes and Spearman Rank